U.S. Liquid Government Liabilities and Emerging Market Capital Flows - Lee, Soyean,Engel, Charles (National Bureau of Economic Research, 2024)
Empirical work finds that flows of investments from the U.S. and other high income countries to emerging markets increase during times of quantitative easing by the U.S. Federal Reserve, and the reverse movement occurs under quantitative tightening. We offer new evidence to confirm these findings, and then propose a theory based on the liquidity of U.S. government liabilities held by the public. We hypothesize that QE, by increasing liquidity, offers greater flexibility for investors that might be concerned their funds will be tied up when shocks to income or investment opportunities arise. With the assurance that some of their portfolio can be readily sold in liquid markets, rich country investors are more willing to increase investments in illiquid loans to emerging markets. The effect of increasing the liquidity of U.S. government liabilities on investments in EMs may even be stronger during times of greater uncertainty
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Geldpolitik; Quantitative Lockerung; Liquidität; Auslandsinvestition; Kapitalmobilität; Schwellenländer; USA; Monetary Policy; Central Banking; and the Supply of Money and Credit; General